2007
DOI: 10.1086/511739
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent Magnetohydrodynamic Self‐similar Extragalactic Jets

Abstract: Extragalactic jets are visualized as dynamic erruptive events modelled by timedependent magnetohydrodynamic (MHD) equations. The jet structure comes through the temporally self-similar solutions in two-dimensional axisymmetric spherical geometry. The two-dimensional magnetic field is solved in the finite plasma pressure regime, or finite β regime, and it is described by an equation where plasma pressure plays the role of an eigenvalue. This allows a structure of magnetic lobes in space, among which the polar a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Examples of knots can be found in the M2-9 Twin Jet Nebula, NGC 5307, and filaments in MyCn 18 Hourglass Nebula, NGC 6543 Cat's Eye Nebula, NGC 2392 Eskimo Nebula, M2-9 Twin Jet Nebula, NGC 6543. In a recent publication (Tsui & Serbeto 2007) of an axisymmetric two-dimensional model, extragalactic polar jets are described from the same self-organizational perspective through an eigenvalue equation with regular eigenfunctions. Jets are driven by plasma pressure to progressively collimate along the polar axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of knots can be found in the M2-9 Twin Jet Nebula, NGC 5307, and filaments in MyCn 18 Hourglass Nebula, NGC 6543 Cat's Eye Nebula, NGC 2392 Eskimo Nebula, M2-9 Twin Jet Nebula, NGC 6543. In a recent publication (Tsui & Serbeto 2007) of an axisymmetric two-dimensional model, extragalactic polar jets are described from the same self-organizational perspective through an eigenvalue equation with regular eigenfunctions. Jets are driven by plasma pressure to progressively collimate along the polar axis.…”
Section: Discussionmentioning
confidence: 99%
“…For the present case, we follow the same apporach but remove the axisymmetric assumption to seek three-dimensional self-similar solutions to model jets, knots, and filaments. Earlier works on temporally self-similar MHD with self-consistent evolution functions include one-dimensional (Osherovich et al 1993(Osherovich et al , 1995 and twodimensional (Tsui & Tavares 2005) cylindrical models of magnetic ropes in the solar-terrestrial environment, two-dimensional axisymmetric model of atmospheric ball lightning in spherical coordinates (Tsui 2006;Tsui et al 2006), active galactic nucleus jets in astrophysical plasmas (Tsui & Serbeto 2007), traditionally treated as a steady state accretion-ejection MHD transport phenomenon from the accretion disk to the polar axis (Blandford & Payne 1982;Pelletier & Pudritz 1992). As for three-dimensional self-similar MHD solutions, there is one earlier case of interplanetary solar magnetic ropes (Gibson & Low 1998), which is not appropriate for astrophysical applications.…”
Section: Self-similar Methods and Self-organizationmentioning
confidence: 99%
“…But the Cinquini-Cibrario equation is interesting in its own right, in connection with normal forms for second-order linear elliptic-hyperbolic equations [1]. Moreover, polar forms of the Cinquini-Cibrario equation arise in models of atmospheric and space plasmas-compare, for example, equation (9) of [5] and equation (19a) of [17] with section 3 of [2]. (Such plasmas are cold, but in a relative rather than absolute sense.)…”
Section: Strong Solutions To Open Boundary Value Problems Consider Amentioning
confidence: 99%
“…We study the expansion of the cavity by applying a self‐similar solution. Substantial work has been done in self‐similarly expanding magnetic structures (Low 1982; Prendergast 2005; Tsui & Serbeto 2007; Gourgouliatos & Lynden‐Bell 2008; Gourgouliatos & Vlahakis 2010; Takahashi, Asano & Matsumoto 2011). Lyutikov & Gourgouliatos (2011) and Dalakishvili et al (2011) have found solutions of force‐free magnetic fields that expand in a self‐similar manner.…”
Section: Introductionmentioning
confidence: 99%